Pelatihan Strategi Digital Marketing Home Industry Terdampak COVID-19 di Desa Bandang Daja - Aulia Dawam; Yusrianto Sholeh (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The development of information and communication technology is very important in the development of the digital business world in Indonesia, which is currently in a state of the covid pandemic. This community service aims to provide training and digital marketing assistance to the home industry in the village of Bandang Daja to be able to improve the economy of the village community, it is necessary to have knowledge about the use of digital marketing applications in this case Canva and social media. This service method is carried out by counseling, discussing, asking questions and continuing with direct practice of using the application. From the results of this activity, the response of the Home Industry owner to the delivery of the material was 80% very understanding and 20% understood. While at the practice stage, the response of the Home Industry owner to the practice session was 90% very understanding and 10% understood. With this training, it is hoped that it can improve the entrepreneurial spirit during the current covid pandemic and have a positive influence on the knowledge of Home Industry owners and their application in digital marketing strategies.